Official attitude of France towards South Africa in the years of crisis, 1899-1902 - Therrode, Elizabeth Cleo (Department of Philosophy, 2023)
France and South Africa - at first ·sight it might seem that these two countries could have had little connection with each other at the turn of the century. In consequence, . it might also seem somewhat unlikely that official French interest could ever have been very great in the largely British-dominated South Africa or that time. But then one thinks of the magic date, 1886, the gold of the Transvaal, and the rush of prospectors, miners, and financiers from all over the globe, and already official French interest, as much as unofficial interest, in, the region, becomes more understandable. Once the existence of that interest has been recognised, a whole series of logical questions arise. It is the object of this thesis to pose and try to answer certain questions, as regards the period 1899 - 1902. Firstly, what basic reasons had the French Government for taking an interest in events in South Africa and changes in the political. structure of the sub-continent in 1899 when the Anglo-Boer war broke out? Secondly, supposing that basic reasons existed for that interest, how did France react officially to the events which led to this conflict and the war itself when it came? Thirdly, why did France choose to react in the way she did? Can the question be answered with reference to a purely South African conte? Finally, what were the results of France's official attitude to South .Africa and the crisis there between 1899 - l902 : that is to say, was the wider course or south A1'rican history or that of France affected by France's attitude? Clearly, the limits of a master's thesis cannot permit a definitive study of this wide subject. Consequently, it is not my intention to attempt to provide here a detailed chronological account of the events which took place before or during the South African War. These events have been sufficiently covered by those better fitted for the task. Instead, only those events which form the essential background to the different points of this thesis, will be mentioned. Furthermore, without indefinitely extending this study, it will also be impossible to deal with every incident in the story of Franco-South African relations and the French official reactions to them. I have not attempted either to include a :full survey of French press reactions to the position of the French Government before and during the War, though such a study would certainly be of considerable interest. Recent work has been carried out on this aspect of the question by a Canadian student, J.G. Pelletier, in a study devoted to French public opinion and the .Anglo-Boer War: "L'Opinion frangaise et la Guerre des Boers" (unpublished Doctoral thesis, Nanterre, 1972). It is appropriate that I indicate here my indebtedness to this important work for illumination on many points with regard to my own thesis. Apart from this last work, I have been able to find only three other works which deal with the subject to French South African relations 1899 - 1902 to any extent, and no single comprehensive work on the subject. Generally, mention of the existence of a French attitude so far as South Africa went at the time, is confined to extremely brief and passing references. The first of the three works is that ot c. Andrew, Theophile Deloasse and the Making or the Entente Cordiale. This book appeared in 1968 and contains two chapters in which the subject of this thesis is handled to a limited degree. Andrew indicates the role in the South African war probably played in the evolution of Anglo-French relations towards the Entente Cordi ale, but it is from this angle alone that he deals ‘with South African - French relations at the turn of the century. Before .Andrew, Pierre Renouvin, an eminent French historian of international relations before the First World War, devoted a couple of paragraphs to the same subject in a work entitled : La Politigue Exterieure de Theo. Delcasse (1898-1905). He too, was solely concerned with indicating the influence of the South African war on Franco-British relations. The third book which contains something about Franco-south African relations during the Anglo-Boer war, is Die Gedenkenalbum van die Tweedevryheidsoorlo&edited by J.H. Breytenbach, in which three or the contributors, F. du T. Spies, J.A. Wiid and A.N. Pelzer, deal with certain different aspects of the question. As they are all concerned with other countries 'reactions to the war as well as that or France, however, their studies are not comprehensive as regards French-South African relations. Numerous works exist which recount the details of President Kruger's visit to France and the strength of pro-Boer public sentiment in France, but the official side of the question is no more than touched on in these books, if at all. Before starting research for this thesis, I had begun work on a subject of purely South African interest. However, marriage interrupted these first efforts. My husband is French, my new home was to be in Paris, and so research in South Africa became impossible.